2020
DOI: 10.1002/anie.201914025
|View full text |Cite
|
Sign up to set email alerts
|

O‐Doped Nanographenes: A Pyrano/Pyrylium Route Towards Semiconducting Cationic Mixed‐Valence Complexes

Abstract: Herein we report an efficient synthesis to prepare O‐doped nanographenes derived from the π‐extension of pyrene. The derivatives are highly fluorescent and feature low oxidation potentials. Using electrooxidation, crystals of cationic mixed‐valence (MV) complexes were grown in which the organic salts organize into face‐to‐face π‐stacks, a favorable solid‐state arrangement for organic electronics. Variable‐temperature electron paramagnetic resonance (EPR) measurements and relaxation studies suggest a strong ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 95 publications
(51 reference statements)
0
32
0
Order By: Relevance
“…The same research group applied the Pummerer oxidative cyclization to the synthesis of more complex O -doped PAHs such as compounds 198 – 200 ( Figure 9 ). Notably, their all-carbon analogues have not yet been synthesized [ 110 ].…”
Section: O -Doped Polycyclic Aromatic Hydrocarbons Embedding Furan Pyran and Oxepine Ringsmentioning
confidence: 99%
“…The same research group applied the Pummerer oxidative cyclization to the synthesis of more complex O -doped PAHs such as compounds 198 – 200 ( Figure 9 ). Notably, their all-carbon analogues have not yet been synthesized [ 110 ].…”
Section: O -Doped Polycyclic Aromatic Hydrocarbons Embedding Furan Pyran and Oxepine Ringsmentioning
confidence: 99%
“…The incorporation of benzoannulated oxygen‐containing heterocycles other than five‐membered is less‐known transformations [55–60] . However, the compounds containing six‐ and seven‐membered rings have some promising applications as OLED materials [61, 62] . To test whether our method is capable of tackling such synthesis, we have obtained fluorinated precursors 19 a and 20 a , which under reactionary conditions transformed into 19 b containing pyrane ring and 20 b containing oxepine ring (Figure 3).…”
Section: Figurementioning
confidence: 99%
“…[55][56][57][58][59][60] However, the compounds containing six-and seven-membered rings have some promising applications as OLED materials. [61,62] To test whether our method is capable of tackling such synthesis, we have obtained fluorinated precursors 19 a and 20 a, which under reactionary conditions transformed into 19 b containing pyrane ring and 20 b containing oxepine ring (Figure 3). Extrapolation of the approach to other oxepines has been proved successful as 21 b and 22 b were obtained in excellent 90 % and 85 % yields.…”
mentioning
confidence: 99%
“…Recently reported semiconducting O-doped polycyclic aromatic hydrocarbons (PAHs), bearing a pyranopyranil or a furanyl core, are very appealing candidates for photoelectronic applications and as p-type semiconductors, showing exceptionally high emission yields and tunable optoelectronic properties in solution. 1 5 Photophysical and electrochemical characterization showed that complementary spectroscopic and redox properties could be tailored through fine tuning of both the π-extension of the carbon scaffold and the oxygen linkages (i.e., furanyl vs pyranopyranyl rings). However, without detailed information about their interfacial electronic properties, the implementation of these complexes into devices would be based on a trial and error method because the coupling to a counter electrode may change the electronic and structural properties of the molecular contact layer, ultimately affecting the efficiency of charge transport of the next molecular layers.…”
Section: Introductionmentioning
confidence: 99%